ANALISA TINGKAT KESEJAHTERAAN KELUARGA PASANGAN MENIKAH USIA DINI KANTOR URUSAN AGAMA (KUA) KECAMATAN BAKI - Nurjianti, N; Baehaqi, B; Sarjono, Joko (Institut Islam Mamba'ul 'Ulum Surakarta, 2023)
Marriage is a phenomenon that is always interesting to discuss in society. Marriage is an important thing for human life, especially in social life in society and survival for the next generation of humans. The phenomenon of early marriage in Baki District has recently been increasing over the last three years. This study aims to analyze what factors influence the occurrence of early marriage and analyze the level of household welfare in couples rising at an early age Religious AffairsOffice in the Baki District.This research is a qualitative descriptive study aimed at getting an overview of the factors that lead to early marriage and the level of family welfare of couples who marry at an early age in the Baki District area. Data collection techniques in this study used direct surveys, interviews and documentation studies. The data analysis technique used in this study uses interactive descriptive analysis.The results of this study draw the conclusion that the main cause of underage marriages in the Baki District area is due to pregnancy out of wedlock which is influenced by the presence of promiscuity factors, educational factors, economic factors and parental encouragement factors. The welfare level of early age couples in the Baki District is included in the pre-prosperous level.